The Pilgrim's progress from this world to that which is to come : delivered under the similitude of a dream / by John Bunyan ; with a memoir of Bunyan, and Macaulay's essay on the Pilgrim's progress ; illustrated with sixty-two engravings on wood, eight colored lithographs, and a fine portrait on steel of Bunyan. - Bunyan, John, 1628-1688, author. (Tufts University. Tisch Library., 2016)
1 online resource (486 pages, 1 unnumbered leaf of plates) : illustrations (some color), portrait.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.